Analisa Kinerja Biaya Green Pada Bangunan Utama Flour Mill Plant Berbasis Value Engineering Dan Life Cycle Cost Analysis - Albert Eddy Husin; Iwan Kurniawan (Jurnal Aplikasi Teknik Sipil, 2023)
In accordance with the mission of the Suistainebale Development Goals 2030, that by 2030 the new building will have a green concept of 100% and an excising building of 60%. With the Value Engineering and Life Cycle Cost Analysis methods, the application of the green concept to the Main Building of the Flour Mill Plant is used for analysis using Structural Equation Modelling – Part Least Square (SEM-PLS). The result of this study is that there are "10 factors that affect the cost performance of the Green project on the Main Building of the Flour Mill Plant", namely Project Manager Performance, Energy Efficiency, Technical Specifications, Provision of Parking Lots, Management Commitments, Water Sources, Analysis Functions, Waste Handling Systems, Selection of Alternative Materials and Energy Costs. The Value Engineering method resulted in cost savings of 14.21% of Green costs, LCCA showed a payback period with time = 3.11 years ≈ 3 years 11 months for the application of the Green concept to the main flour mill plant building.Sesuai misi dari Suistainebale Development Goals 2030, bahwa pada tahun 2030 banguan baru berkonsep hijau sebesar 100% dan bangunan ekisting sebesar 60%. Dengan metode Value Engineering dan Life Cycle Cost Analysis, penerapan konsep green pada Bangunan Utama Flour Mill Plant digunakan analisis dengan menggunakan Structural Equation Modelling – Part Least Square (SEM-PLS). Hasil dari penelitian ini adalah terdapat “10 faktor yang berpengaruh kepada kinerja biaya pada proyek Green pada Bangunan Utama Flour Mill Plant” yaitu Project Manager Performance, Efisiensi Energi, Spesifikasi Teknis, Penyediaan Lahan Parkir, Komitmen Manajemen, Sumber Air, Fungsi Analisis, Sistem Penanganan Sampah, Pemilihan Material Alternatif dan Biaya Energi. Metode Value Engineering menghasilkan penghematan biaya sebesar 14,21% dari biaya Green, LCCA menunjukkan pembayaran kembali (Payback Period) dengan waktu = 3,11 Tahun ≈ 3 Tahun 11 Bulan untuk penerapan konsep Green pada bangunan Utama Flour Mill Plant.